In Silico Coformer Screening for Mefenamic Acid Cocrystallization - Hidayat, Aulia Fikri; Fakih, Taufik Muhammad; Darma, Gita Cahya Eka; Choesrina, Ratu (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Cocrystallization is a widely used approach to enhance the solubility and dissolution characteristics of poorly soluble drugs. A pharmaceutical cocrystal is a multicomponent system composed of a solid active pharmaceutical ingredient (API) and a coformer, governed by non-covalent interactions. Screening for suitable coformers is essential to obtain an optimal cocrystal for specific drugs. This study aims to determine the drug-coformer interactions to select the most suitable coformer for cocrystal formation using the molecular docking method. Mefenamic acid, classified as a class II drug in the biopharmaceutical classification system (BCS), was used as the model drug. Two-dimensional structures of mefenamic acid (PubChem CID: 4044) and potential coformers were sourced from PubChem. Geometric optimization of all compounds was performed using GaussView 5.0.8 and Gaussian09 with the 3-21G basis set and Density Functional Theory (DFT) B3LYP method. The optimized compounds were prepared by adding hydrogen atoms and calculating Kollman partial charges using AutoDock 4.2. A grid box of size 40 Å × 40 Å × 40 Å was generated, with a maximum radius of 0.375 Å set as the surface distance in each simulation. A hundred conformations were run using the Lamarckian Genetic Algorithm. Interaction types and binding energies were analyzed using VMD 1.9.2 and BIOVIA Discovery Studio 2020 to compare interactions between mefenamic acid and each coformer. The results revealed that most coformer compounds formed interactions with mefenamic acid via hydrogen bonding and π–interactions. Saccharin demonstrated the most optimal interaction with mefenamic acid, with a binding free energy of –3.1 kcal/mol. Saccharin was identified as the most suitable coformer for mefenamic acid cocrystal formation based on the molecular docking study. Further experimental validation of saccharin is recommended to confirm its effectiveness in cocrystallization with mefenamic acid.